Utilization of Social Media Marketing By Young Business Players in Binjai City in Developing Customer Equity - T. Enita Rosmika; Amrin Mulia Utam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Various lines of business and marketing in all dimensions of the world have been digitized, the use of social media by business actors has had a major influence in introducing their products more effectively and efficiently, the role of social media in increasing sales and building communities is more targeted than conventional media use. This research study aims to analyze the use of social media by young entrepreneurs in the variable consumption, curation, creation and collaboration with customer equity in young entrepreneurs in Binjai City. The methods used were questionnaires and interviews as well as direct field surveys. The results obtained state that social media Instagram or Facebook is preferred compared to others as a means of promotion for business people, women entrepreneurs prefer Instagram. From male entrepreneurs. The results also show that the use of social media in marketing has a positive and significant effect on customer equity in young entrepreneurs in Binjai City.